Revolutionizing photocatalysis: Synergistic enhancement of structural, optical, and photodegradation properties in Be-doped V2O5 nanoparticles for efficient methylene blue removal - Karamat, Ansa; Khan, M.I.; Mujtaba, Ali; Atif, Muhammad; Zar Muaawia, Abu; Flores-Valenzuela, J.; Ali, Babar; Shahid, Wajeehah; Hussain, Saddam (Results in Chemistry, 2024)
[Display omitted] This study focuses on the investigation of beryllium (Be) doping in V2O5 nanoparticles and the coordinated effects it has on the structural, optical, and photocatalytic characteristics of the material. XRD analysis reveals modifications in the orthorhombic structure upon Be doping, decreasing crystallite size (68.7–46.6 nm), and increased dislocation line density. Optimizing charge carrier mobility and separation is crucial for improving photocatalytic activity, and this is achieved via these adjustments. Raman spectra indicated increased crystallinity with Be doping. The optical analysis demonstrated an adjustable band gap (2.47–2.60 eV) and reduced refractive index (2.49–2.45), that enhance light absorption efficiency. More importantly, the study shows that Be-doped V2O5 nanoparticles have better photocatalytic activity for the breakdown of methylene blue, indicating its potential for environmentally friendly remediation. The present work contributes to the advancement of customized doping approaches for maximizing V2O5 functioning across a range of applications by clarifying the complex impacts of Be doping.